Pengaturan Dasar Hukum dalam Pelaksanaan Telemedicine pada Fasilitas Kesehatan Tingkat Pertama - Leonardus Susilo (Masyarakat Hukum Kesehatan Indonesia, 2022)
Telemedicine use in Indonesia has drastically increased since the pandemic era begins and it will continue to grow into the future. The primary care in Indonesia also called Fasilitas Kesehatan Tingkat Pertama (FKTP) will get the advantages from telemedicine with its rehabilitative, preventive, rehabilitative, and curative care, and also FKTP has a massive number of members. This study aims to analyze aspects that need to be regulated in drafting telemedicine regulations, especially in FKTP. This study was conducted by analyzing telemedicine regulation in Indonesia and another study that relates to the implementation of telemedicine. In Indonesia, telemedicine regulation is for Covid cases only, but telemedicine is being used very widely in various cases. There is an omission of the legal basis in its implementation so it needs to be regulated carefully and quickly. Things that need to be considered are administrative aspects: patient authentication, doctor’s license, and patient-doctor relation in telemedicine; patients rights: information, consent, and confidentiality; quality of medical care: competency standard, and medical device standard.